Protective effect of melatonin and omeprazole against alendronat-induced gastric damage - ŞENER, GÖKSEL (SPRINGER, 2005)
Alendronate causes serious gastrointestinal adverse effects. We aimed to investigate if free radicals have any role in the damage induced by alendronate and if melatonin or omeprazole is protective against this damage. Rats were administered 20 mg/kg alendronate by gavage for 4 days, either alone or following treatment with melatonin or omeprazole. On the last day, following drug administration, pilor ligation was performed, and 2 hr later rats were killed and stomachs were removed. Gastric acidity and tissue ulcer index values, lipid peroxidation, and myeloperoxidase and glutathione levels, as well as the histologic appearance of the stomach tissues, were determined. Chronic oral administration of alendronate induced significant gastric damage, increasing lipid peroxidation and myeloperoxidase activity, while tissue glutathione levels decreased. Treatment with omeprazole or melatonin prevented this damage as well as the changes in biochemical parameters, and melatonin appeared to be more efficient than omeprazole in protecting the mucosa. Intraperitoneal administration of alendronate did not cause much gastric irritation. Findings of the present study suggest that alendronate induces oxidative gastric damage by a local irritant effect and that melatonin and omeprazole are protective against this damage due to their antioxidant properties.
Keywords: alendronat; omeprazole; melatonin; lipid peroxidation; glutathione; myeloperoxidase; LIPID-PEROXIDATION; BRAIN-REGIONS; BISPHOSPHONATES; INJURY; MECHANISMS; RATS; MYELOPEROXIDASE; REPERFUSION; GLUTATHIONE; ESOPHAGEAL